Twenty Second Century Artificial Intelligence - Satish Gajawada; Hassan M. H. Mustafa (Twenty Second Century Artificial Intelligence, 2021)
The book defines various new paths as nine different chapters. First, second and third chapters deal with “Artificial Human Optimization”, “Artificial Soul Optimization” and “Artificial God Optimization” respectively. Three new branches titled “Artificial Satisfaction”, “Deep Loving” and “Nature Plus Plus Inspired Computing” are shown in fourth, fifth and sixth chapters respectively. The seventh chapter describes “Artificial Heart Neural Networks” where algorithms are created by taking inspiration from both Heart and Brain. Two new branches “Artificial Excellence” and “Stories Inspired Optimization Algorithms” are created in last two chapters of this book.